Gender diversity and firm performance: evidence from technology and industrial companies - Zhang, Xinran (2022)
Due to women’s rights movement and a growing number of women in the workplace, the relationships between gender diversity and firm performance become topical issues. To investigate the relationship, I examined data from 79 companies in the technology industry and industrial industry between 2016 and 2020. This research uses the quantitative method and ordinary least square regression and two-step GMM regression are used to test the sample. The results suggest that board gender diversity is significant and positive related to Tobin’s Q but has no link with ROE. It is also discovered that the workforce gender diversity has no link with ROE and is negatively correlated with firm Tobin's Q. In addition, the results reveal that the impacts of gender diversity vary on industries. These results could support the agency theory, critical mass theory, resource dependency theory, and social identity theory. In addition, this could provide implications for human resource management and board composition. Different from previous studies, this paper emphasizes the importance of the number of women employees and the different impacts on the technology industry and industrial industry. However, future studies could further investigate the impact of women in the workforce and consider more factors such as qualitative factors and contextual differences.